Regional Economic Impacts of the Øresund Cross-Border Fixed Link: Cui Bono? - Michael Funke; Kadri Männasoo; Helery Tasane (Center for Economic Studies and ifo Institute (CESifo), 2023)
Recently, there has been a growing interest in newly developed econometric tools to conduct counterfactual analysis when a treated unit experiences a policy intervention, and an artificial control group has to be constructed. Adopting novel penalized synthetic control methods, we quantify the causal impact of the multi-modal Øresund fixed link on the adjacent cross-border regions in Skåne and Zealand. The treatment impacts on the intertwining metropolitan regions of Copenhagen and Malmö are positive. However, the impact on the Copenhagen metropolitan area is overlaid by the Great Belt strait fixed link, which was opened shortly before. An array of robustness tests supports our interpretations, and several appendices supplement the presentation in the paper.
Keywords: C21; C54; H54; O11; R12; R42; 330; Øresund fixed link; cities; infrastructure; economic development; synthetic control method